MARINE AND COASTAL RESOURCES AND THE ECONOMIC VALUES OF TOGEAN ISLANDS, CENTRAL SULAWESI - Suwarno, Yatin; Nahib, lrmadi (MAJALAH ILMIAH GLOBE, 2008)
The location of the research is Togean Island, located in the middle of Tomini Bay, Province of Central Sulawesi - Indonesia. The objectives of the research are: to know the present potential, the degradation trend, and the economic values of marine and coastal resources at Togean Island. The methods for resources inventory used remote sensing and geographic information system technologies. Resources economic valuation by using travel cost method, effect on production method, and benefit transfer method. The results of this research are especially for coral reef and mangrove ecosystem. The total area of coral reef ecosystem at Togean island is 36,834.12 Ha, can be classified as 30,116.71 Ha (81%) of coral reef, 1,343.24 Ha (4%) of sea grass, and 5,374.17 (15/r) of sand. Within ten year (1997-2007), coral reef has decreased 91.07 Ha, but sea grass and sand have increased 25.46 Ha and 65.61 Ha. The kinds of coral reef typologies completed: fringing reef, barrier reef, path reef, and atoll. Economic values of coral reef ecosystem as ecotourism based on travel cost method was Rp. 1,6 649,062.000/year (US $ 1,664,906.2/year) and coral fish production based effect on production was Rp 68,417,000/year (US $ 6,841.7/year). The total area of mangrove ecosystem at Togean Island was 11,932.81 Ha, and were classified into 4 (four) classes: low density area was 2,979.52 Ha (24.97%), moderate density area was 1,504.95 Ha (12.61%), high density area was 4,046.74 (33.91%^), and non-forest was 3,228.65 Ha (27.06%). Within ten years (1997-2007), low density mangrove has decreased 1,485,836 Ha; non forest has decreased 2,651,855 Ha. Otherwise, mangrove moderate density and mangrove high density have increased 3,244,543 Ha and 1,005,475 Ha. One of mangrove ecosystem direct use value is potency of mangrove crab (Scitta serrata), with the total benefit of Rp. 3,465,600,000/year (US$ 346,560/year). Indirect use value based on replacement cost for coastline buffer (break water) was Rp. 467,723,000,000/year (US $ 46,772,300/year)Keywords : Marine and Coastal Resources, Economic ValueABSTRAKLokasi penelitian adalah Kepulauan Togean, yang terletak di tengah Teluk Tomini Provinsi Sulawesi Tengah Indonesia. Tujuan dari penelitian adalah: untuk mengetahui potensi sekarang, tren degradasi, dan nilai-nilai ekonomi dari sumberdaya laut dan pesisir di Kepulauan Togean. Metode untuk inventarisasi sumber daya digunakan remote sensing dan teknologi sistem informasi geografis. Penilaian ekonomi sumber daya dengan menggunakan metode biaya perjalanan, efek pada metode produksi, dan keuntungan metode transfer. Hasil dari penelitian ini adalah terutama bagi ekosistem terumbu karang dan ekosistem mangrove. Luas wilayah ekosistem terumbu karang di Kepulauan Togean 36,834.12 Ha dapat diklasifikasikan sebagai terumbu karang 30,116.71 Ha (81%), rumput laut adalah 1,343.24 Ha (4%), dan pasir adalah 5,374.17 (15%). Selama sepuluh tahun (1997-2004), terumbu karang penurunan 91,07 Ha, tetapi rumput laut dan pasir meningkat 25,46 Ha dan 65,61 Ha. Jenis -jenis terumbu karang tipologi selesai: renda karang, karang penghalang jalan karang, dan atol. Nilai ekonomi ekosistem terumbu karang sebagai ekowisata didasarkan pada metode biaya perjalanan sebesar Rp. 16,649,062.000/tahun (US $ 1,664,906.2/tahun) dan produksi ikan karang efek didasarkan pada produksi adalah Rp 68.417.000/tahun (US $ 6,841.7/tahun). Luas wilayah ekosistem mangrove di Kepulauan Togean 11,932.81 Ha, dikelompokkan menjadi 4 (empat) kelas: daerah kepadatan rendah adalah 2,979.52 Ha (24,97%), kawasan kepadatan sedang 1,504.95 Ha (12,61%), daerah kepadatan tinggi adalah 4,046.74 ( 33,91%), dan non hutan adalah 3,228.65 Ha (27,06%). Selama sepuluh tahun (1997-2007), kepadatan rendah bakau penurunan 1.485.836 Ha; non penurunan hutan 2.651.855 Ha. Jika tidak, moderat mangrove mangrove kerapatan dan kepadatan tinggi meningkat 3.244.543 Ha dan 1.005.475 Ha. Salah satu ekosistem mangrove nilai pakai langsung potensi mangrove adalah kepiting (Scilla serrata), total keuntungan adalah Rp. 3.465.600.000/tahun (US $ 346.560 / tahun). Nilai pakai tidak langsung didasarkan pada biaya penggantian untuk penyangga pantai (break air) adalah Rp. 467.723.000.000/tahun (US $ 46.772.300 / tahun).Kata Kunci: Pesisir dan Laut, Sumber Daya, Nilai EkonomiÂ